NATIONAL HEALTH INSURANCE BASED TELEMEDICINE APPLICATION FOR HYPERTENSION MANAGEMENT IN PRIMARY LEVEL OF HEALTH FACILITIES - Saputra, Pandit Bagus Tri; Izzati, Nabila; Rosita, Primadita Esther; Trilistyoati, Desy; Isyroqiyyah, Nur Moya; Hasna, Iffa Halimah; Putri, Niamita Eka Puspita; italoka, Ervina Dyah; Putra, Muhammad Rifqi Arya; Rahman, Andi Lestari; Djuari, Lilik (Journal of Community Medicine and Public Health Research, 2021)
Hypertension nowadays still becomes one of the severe problems in Indonesia, with a prevalence of 34% in 2018. The complication of hypertension causes the most deaths and disabilities in Indonesia and cost 75% of The Social Security Organizing Agency (BPJS) budget or IDR 15 trillion in 2019. This problem was probably caused by patients' lack of knowledge and limited personnel at the primary health centre (PHC). Telemedicine is a health care provider without any direct contact, which has various methods. Today, telemedicine in Indonesia is growing rapidly along with technology and legal regulation in its implementation, increasing users by 700% in the first year of 2020. Despite the rise of those numbers, telemedicine in PHC is still limited. Recently, the Ministry of Health and various organizations have issued telemedicine regulations at primary level health facilities in collaboration with The Social Security Organizing Agency. This review aims to discuss the current implementation and the potential future of telemedicine-based hypertension management in collaboration with the Social Security Organizing Agency in PHC.